2007
DOI: 10.1111/j.1365-2486.2007.01347.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant nitrogen acquisition and interactions under elevated carbon dioxide: impact of endophytes and mycorrhizae

Abstract: Both endophytic and mycorrhizal fungi interact with plants to form symbiosis in which the fungal partners rely on, and sometimes compete for, carbon (C) sources from their hosts. Changes in photosynthesis in host plants caused by atmospheric carbon dioxide (CO 2 ) enrichment may, therefore, influence those mutualistic interactions, potentially modifying plant nutrient acquisition and interactions with other coexisting plant species. However, few studies have so far examined the interactive controls of endophyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 62 publications
2
36
0
Order By: Relevance
“…AM fungal colonization significantly improved N accumulation regardless CO 2 concentrations, and the greater 15 N recovery rate in the AM plants grown under elevated CO 2 further indicated the enhanced N uptake by those plants. Similar to these findings, enhanced N accumulation and uptake under elevated CO 2 concentration has been reported in AM plants of Trifolium repens (Gamper et al 2005), P. lanceolata (Chen et al 2007), Avena fatua (Cheng et al 2012), and in newly established grassland communities (Zavalloni et al 2012). The higher biomass and hence greater N demand of AM plants grown under CO 2 enrichment may partly explain the increased N accumulation.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…AM fungal colonization significantly improved N accumulation regardless CO 2 concentrations, and the greater 15 N recovery rate in the AM plants grown under elevated CO 2 further indicated the enhanced N uptake by those plants. Similar to these findings, enhanced N accumulation and uptake under elevated CO 2 concentration has been reported in AM plants of Trifolium repens (Gamper et al 2005), P. lanceolata (Chen et al 2007), Avena fatua (Cheng et al 2012), and in newly established grassland communities (Zavalloni et al 2012). The higher biomass and hence greater N demand of AM plants grown under CO 2 enrichment may partly explain the increased N accumulation.…”
Section: Discussionsupporting
confidence: 70%
“…However, the mechanisms underlying this phenomenon remain unknown. These and previous observations suggest that AM fungal mediated plant N uptake and partitioning is a complicated process and merits further investigations (Chen et al 2007;Cavagnaro et al 2011).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Furthermore, Chen et al (2007) have suggested that endophytes may not affect mycorrhizal colonisation directly.…”
Section: Introductionmentioning
confidence: 98%